The impact of summer Yangtze river runoff fluctuations on estuarine fronts dynamics and zooplankton communities from 2016 to 2023 - Yepeng Xu; Fangping Cheng; Xiao Ma; Ming Mao; Yuanli Zhu; Zhibing Jiang; Ziting Zheng; Jiangning Zeng; Lu Shou; Feng Zhou; Ping Du (Frontiers in Marine Science, 2025)
Estuarine fronts, which arise from the convergence of distinct water masses, exhibit considerable spatial and temporal variability and play a crucial role in shaping ecological dynamics within estuarine ecosystems. Despite their importance, due to limited data, there’s inefficiency understanding on how biological communities, particularly zooplankton, respond to these dynamic environmental features. The Yangtze River Estuary (YRE), a transitional zone between the Yangtze River and the East China Sea, is an ideal place in which to study the response of zooplankton communities to estuarine fronts, as freshwater discharge, offshore waters, and the Taiwan Warm Current converge here and form sediment and plume fronts in summer. We investigate zooplankton communities and environmental variables including temperature, salinity, turbidity, and Chlorophyll a (Chl a ) in the YRE during summer from 2016 to 2023, and examine the differences in spatial distribution of estuarine fronts and zooplankton community and the dominant environmental factors controlling zooplankton variation in different runoff years. Our findings found that the sediment fronts appeared around 122.5°E except in drought years (2022 and 2023); the plume fronts extended to 123.5°E and beyond during wet years (2016, 2020 and 2021), while shrank within 123°E in drought years. The zooplankton communities were classified into low-salinity, moderate-salinity, and high-salinity groups spatially in most years, but the low-salinity group had not been detected in the extreme drought year 2022. During flood years, low-salinity nearshore species such as Oithona brevicornis , Centropages dorsispinatus and Cladocera exhibited a notable increase in dominance, while the drought favored euryhaline species like Microsetella rosea . Furthermore, the turbidity, salinity and temperature all played significant roles in zooplankton spatial variation in wet years, while only salinity played as an important factor in drought years. These results implied the prominent sediment fronts and extended plume fronts in wet years shaped the zooplankton spatial variation collectively; in contrast, sediment fronts disappeared during drought years, and the plume fronts played a crucial role in shaping the zooplankton spatial variation. Besides, the extremely low runoff in 2022 has been shown to lead to obvious changes in zooplankton communities, which might affect fisheries stocks and require concern.